An investigation of the child-friendly environmental status of primary schools in terms of nature of classrooms (2008)
This study investigated the extent to which the environment of our primary school classrooms is child-friendly in terms of nature of classrooms. The sample comprised the head teachers of 165 primary schools in the urban and rural areas of Abia State. Data collection involved the use of a validated Child-friendly Environmental Status Inventory (CFESI). The data were analysed using frequency counts and percentages. The results indicate that the child-friendly environmental status of classrooms in the primary schools varied widely and depended very much on school type. However, there was no school in which the child-friendly environmental status of the classrooms was 0% or 100%. The implications of these findings for teaching-learning condition in primary schools are discussed.